Non-fatal suicidal self-poisonings in children and adolescents over a 5-year period (2007-2011) - Zakharov, Sergey; Navratil, Tomas; Pelclova, Daniela (Basic & clinical pharmacology & toxicology, 2013)
The objective of this study was to analyse non-fatal suicidal self-poisonings in children and adolescents and to identify commonalities that might direct preventive health efforts. From the database of the Czech Toxicological Information Center, the inquiries due to non-fatal suicidal self-poisonings in children (9-13 years old) and adolescents (14-18 years old) in 2007-2011 were evaluated. From 10,492 calls about suicide attempts, 2393 concerned children and adolescents (13.5% and 86.5%, respectively). Most suicide attempts were committed during the spring (31.3%). Among toxic agents, drugs were used in 97.8% of the cases. 63% of cases involved monopoisonings and combinations of more than three drugs (10.3%) were rare. The most frequent ingestions appeared using drugs affecting the nervous system and anti-inflammatory non-steroids. The dose was evaluated as toxic in 73.4% of the cases and as severely toxic in 3.0% of the cases. The symptoms of moderate and severe intoxications were present in 10.5% of the cases. First aid was provided in 5.6%, and gastric lavage was performed in 21.9% of the cases. Antidotes were indicated in 13.3% and secondary elimination methods in 4.4% of the cases. Mostly, one or two easily accessible drugs were used in suicide attempts, with paracetamol and ibuprofen were the most common ones. Only one in 10 children applied a non-toxic dose. One-fifth of the patients received medical care within 60 min. and one-third later than 4 hr after exposure. The time criterion for gastric lavages was fulfilled in less than half of the cases, and in every fourth case, the procedure was performed when it was unlikely to be beneficial.
Keywords: Sex Factors; Humans; dítě; Suicide, Attempted; Child; Female; lidé; Poisoning; sexuální faktory; roční období; ženské pohlaví; Male; Adolescent; Seasons; Czech Republic; otrava; pokus o sebevraždu; Česká republika; mužské pohlaví; mladiství